2011
DOI: 10.1093/ndt/gfr695
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cell-free DNA promotes inflammation in haemodialysis patients

Abstract: We provide the first evidence that cfDNA has selective immunostimulatory effects on human monocytes. This process may contribute to the proinflammatory milieu observed in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 20 publications
2
75
2
3
Order By: Relevance
“…First discovered in 1948 by Mandel and Metais, fragmented DNA or cfDNA has since been associated with a number of conditions, including end-stage renal disease, myocardial infarction, stroke, and trauma [2][3][4][5][6][7]. Multiple studies have shown a correlation between the levels of cfDNA and cellular injury and necrosis, processes relevant in cancer cell survival and propagation.…”
Section: Cfdnamentioning
confidence: 99%
“…First discovered in 1948 by Mandel and Metais, fragmented DNA or cfDNA has since been associated with a number of conditions, including end-stage renal disease, myocardial infarction, stroke, and trauma [2][3][4][5][6][7]. Multiple studies have shown a correlation between the levels of cfDNA and cellular injury and necrosis, processes relevant in cancer cell survival and propagation.…”
Section: Cfdnamentioning
confidence: 99%
“…Other studies have shown that cfDNA exists at a ready-state level in clinical scenarios such as myocardial infarction, surgery, trauma and stroke. Cellfree DNA may increase dramatically with cellular injury or necrosis [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…6,[17][18][19][20][21] NETs are composed of extracellular DNA, histones, and neutrophil granular proteins. CFDNA, either in the presence or absence of histones, has been shown to modulate several procoagulant pathways.…”
mentioning
confidence: 99%